IMPLEMENTASI E-GOVERNMENT TRANSFORMASI DIGITAL LAYANAN KEPEGAWAIAN “SITAGUH” PADA BADAN KEPEGAWAIAN DAERAH PROVINSI KALIMANTAN TENGAH - Oktobrian, Ivan; Bernardianto, Raden Biroum; Saipul, Saipul (Pencerah Publik, 2025)
This study explores the implementation of digital transformation in civil service management through the "SITAGUH" application at the Regional Personnel Agency (BKD) of Central Kalimantan Province. As a digital civil service platform, SITAGUH is designed to enhance the efficiency, transparency, and accessibility of public services in the field of civil servant administration. The research adopts a qualitative descriptive approach, utilizing data collection methods such as interviews, observations, and document analysis to assess the effectiveness and challenges associated with the implementation of the SITAGUH system. The findings indicate that SITAGUH successfully improves service quality by streamlining manual processes and accelerating service delivery. Nevertheless, the implementation also encounters challenges, including a lack of IT-skilled human resources among civil servants and the need for ongoing system training and socialization. This study contributes to the broader discourse on e-government and underscores the importance of strategic planning and continuous improvement in achieving successful digital transformation within public service institutions